Peningkatan Pemasaran UMKM Melalui Kolaborasi E-Commerce dan Instagram - Sabtu Sabtu; Abd. Basith; Al Rusman; Ali Basriadi; Alex Sandri Sikumbang; Didin Setyawan; Doni Syofiawan (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2024)
This community service project aims to enhance SME marketing through the collaboration of e-commerce and Instagram. Through specially designed training, SME participants were taught how to effectively utilize these platforms to market their products. The study employs both quantitative and qualitative approaches to evaluate the effectiveness of the training. Data were collected through questionnaires, interviews, and direct observations. The results indicate a significant increase in participants' knowledge and skills, as well as an improvement in sales after the training. These findings support the Diffusion of Innovations theory and integrated marketing communications, demonstrating that the collaboration of e-commerce and Instagram can enhance SME competitiveness. Recommendations include developing training materials, providing ongoing support, establishing partnerships with e-commerce and social media platforms, and conducting periodic evaluations.